Thermal efficiency of vertical and horizontal-finned solar collector integrated with forced air circulation dryer for Apple as a sample. Issue 5 (4th April 2019) - Al-Neama, Maytham Ali; Farkas, Istvan
Abstract: In this article, an experimental estimation of thermal efficiency of horizontal and vertical-finned double-pass solar air collectors integrated with drying chamber has been carried out. The rig consists of two main parts as solar collector and dryer. The system was installed in the laboratory of Szent István University, Gödöllő, Hungary. The absorbers were made from a copper integrated fins in horizontal and vertical directions. The test results showed that the daily efficiency increased by10% when the direction of fins have been changed from vertical to horizontal. After 5 h drying of 2 kg apple slices, the final weights were 1.16 and 1.37 kg by using horizontal and vertical-finned collectors, respectively.